KONTRIBUSI KEPERCAYAAN DIRI TERHADAP HASIL BELAJAR KETERAMPILAN BERMAIN BULUTANGKIS BERDASARKAN TINGKAT KECEMASAN - Arief, Muhammad Fadillah (2014)
Penelitianinibertujuanuntukmengujibesarnyakontribusikepercayaandiriterhadaphasilbelajarketerampilandasarbermainbulutangkisberdasarkantingkatkecemasan.Penelitiandilakukanmenggunakanmetodedeskriptifkuantitatifterhadap80 orang siswa (40puteradan40puteri) yang berusia 10-12 tahun di SDMuhammadiyah 3 Bandung.Data dikumpulkanmenggunakanskalakepercayaandiri, skalakecemasandantesketerampilandasarbermainbulutangkis (servispanjangdan lobbertahan).Mengujivaliditas data skalakecemasandianalisismenggunakananalisisekspolatorifaktordenganfaktor loading 0.788, skalakepercayaandirimenggunakananalisiskonfirmatorifaktordenganfaktor loading 0.760.UjireliabilitasmenggunakanCronbachAlpha skalakecemasan0,942 danskalakepercayaandirimempunyaireliabilitas0,826. Hasilujiasumsianalisislinearitasuntukmengetahuihubunganantarvariabeldengansignifikasi 0.000 metode yang digunakanadalah< 0,05. Hasilujihipotesismenunjukanbahwaterdapathubungannegatifantarakepercayaandiridankecemasansebesar -0,903 danhasilujiModeratRegresion Analysis (MRA)menujukanbahwaterdapatkontribusikepercayaandiritethadaphasilketerampilandasarbermainbulutangkisberdasarkantingkatkecemasanyaitusebesar52,6%. HasilujiRegresikepercayaandiridengantingkatkecemasantinggimemberikankontribusisebesar30,5% sedangkankepercayaandiridengantingkatkecemasanrendahmemberikankontribusisebesar14,8%. This study is intended to figure out to what extent the contribution of self-confidence on badminton learning outcome based on anxiety level. The studyis carried out by using descriptive quantitative method on 80 students (40 males and 40 females) whose ages range from 10 to 12 years old in SD Muhamadiyah 3 Bandung as participants. The data are collected by employing the scale of self-confidence, scale of anxiety, and a test to measure the students' skill in badminton (in terms of long serve and defense lob). The data obtained from the scale of anxiety are analyzed by using explanatory factor analysis to test its validity with 0.788factor-loading, while the factor loading of the scale of confidence is 0.760.Cronbach Alpha is used to measure the reliability of both scales. The result shows a value of 0,942 for the self-confidence scale and 0,826 for the anxiety scale. The result of assumption trial using linearity analysis to find out the relationship between the variables with 0.000 significance method is < 0,05. The hypothesis testing shows that there is a negative correlation between self-confidence and anxiety by -0,903. Moderate Regression Analysis(MRA) was used to find out that there is a contribution of self-confidence to anxiety by 52,6%.High level of confidence contribute 30,5% and low level of confidence contributes 14,8%, while the rest is influenced by uninvestigated factors.